Socio-Demographic Factors Affect the Prevalence of Hematuria and Proteinuria Among School Children in Hualien, Taiwan: A Longitudinal Localization-Based Cohort Study - Chen, Ming-Chun; Wang, Jen-Hung; Chen, Jui-Shia; Chang, Yung-Chieh; Jan, Rong-Hwa; Yang, Shang-Hsien; Chu, Shao-Yin; Lai, Pei-Chun; Chu, Chia-Hsiang; Cheng, Ching-Feng; Chang, Yu-Hsun (Frontiers in Pediatrics, 2020)
Objective Child hematuria/proteinuria is a risk factor for chronic kidney disease (CKD) in later life, and mass urinary screening could detect asymptomatic glomerulonephritis at an early stage. This study aimed to evaluate the longitudinal prevalence of hematuria/proteinuria and its association with socio-demographic factors among school children in Hualien, Taiwan. Methods The study cohort consisted of first and fourth graders enrolled from 2008 to 2015 in Hualien. We combined the data from two consecutive health examinations to ensure the validity of the body mass index (BMI), urbanization, proteinuria, and hematuria grouping. Prevalence and health status differences between sex, age, BMI, and urbanization level were examined. Results A total of 16,990 students within the same BMI and urbanization categories were included during the study interval. The prevalence of persistent hematuria was 1.0%. Fourth graders (odds ratio OR: 1.68, p = 0.002), girls (OR:1.48, p = 0.014), and students from suburban/rural areas (OR:1.99, and OR:4.93, respectively; both p <0.001) demonstrated higher hematuria risk. The prevalence of proteinuria was 0.2%. Fourth graders (OR: 4.44, p <0.001) and students in suburban areas (OR:0.27, p = 0.031) were associated with persistent proteinuria. After stratifying by age, the significant association remained. A higher risk of proteinuria was noted in underweight subjects (OR:2.52, p = 0.023) among the fourth-grade students. Conclusion The prevalence of hematuria/proteinuria in Hualien was higher than the average reported for Taiwan. Hematuria/proteinuria was significantly associated with sex, age, BMI, and urbanization. Our longitudinal results can provide information for future pediatric CKD prevention in Taiwan.